1998
DOI: 10.1177/154193129804200311
|View full text |Cite
|
Sign up to set email alerts
|

An Absence of Vigilance Decrement in a Complex Dynamic Task

Abstract: Although it is sometimes stated that there is a danger of a loss of vigilance in supervisory tasks where the main task is monitoring, there appears to be no experimental research on the vigilance decrement in complex realistic tasks. In this paper we report an experiment on the detection of dynamic faults in a rather complex microworld, PASTEURISER. An overall decrement in target detection was found, but no vigilance decrement as a function of time during the first 30 minutes or 1 hour. Even when the system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In stage 1, where the sample consisted of operators treated as a single sample, no statistically significant vigilance decrements or increments were found over the ninety-minute period. This is consistent with some studies of complex vigilance tasks that are similar to real world jobs (e.g., Molloy and Parasuraman, 1996;Moray and Haudegond, 1998;Tickner and Poulton, 1975). However, in view of the mixed findings regarding vigilance decrements in complex tasks, we examined the potential reasons for this and alternative explanations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In stage 1, where the sample consisted of operators treated as a single sample, no statistically significant vigilance decrements or increments were found over the ninety-minute period. This is consistent with some studies of complex vigilance tasks that are similar to real world jobs (e.g., Molloy and Parasuraman, 1996;Moray and Haudegond, 1998;Tickner and Poulton, 1975). However, in view of the mixed findings regarding vigilance decrements in complex tasks, we examined the potential reasons for this and alternative explanations.…”
Section: Discussionsupporting
confidence: 85%
“…Anecdotal evidence suggests that operator attention drifts after 15 min (Security Park, 2001), but this has not been examined in relation to detection performance and it is not clear whether this applies to all operators. Although there is the potential for vigilance decrements in work requiring vigilance, inconsistent results regarding the existence of vigilance decrements have been found in complex tasks (Adams et al, 1961) and tasks that are similar to those performed in real world settings (Hollenbeck et al, 1995;Molloy and Parasuraman, 1996;Moray and Haudegond, 1998;Pigeau et al, 1995). In view of variations in the information processing requirements of different vigilance intensive jobs and the numerous factors that affect vigilance performance, this is not surprising.…”
Section: Introductionmentioning
confidence: 99%
“…Parasuraman 1986). Classical vigilance decrements are associated with very simple signals, such as those generated by radar or sonar systems, and, although there has been some discussion of classical vigilance decrements in the supervisory control of complex systems, there is little evidence that they are of importance Haudegond 1997, 1998). Those concerned with possible`complacency' in complex automated systems suggest that an incorrect strategy which causes sub-optimal monitoring is more important (Parasuraman et al 1993, Billings 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Against our pre-registered hypothesis, we did not replicate the findings of Luna et al 56 , as the single and dual load conditions both showed a significant EV decrement with time-on-task, without any differences across load conditions. Some studies report similar null effects comparing single and dual tasks 32 , 72 , or no vigilance decrement at all regardless of the load condition 73 , 74 . However, most of the literature is either skewed towards underload (observing larger decrements with lower task demands 44 or higher engagement 75 ) or overload theories (observing greater vigilance decrements with increased task demands by adding a secondary task 39 41 or increasing instruction complexity 72 ), without any clear consensus.…”
Section: Discussionmentioning
confidence: 93%